2013
DOI: 10.1089/bsp.2012.0071
|View full text |Cite
|
Sign up to set email alerts
|

A Generic Open-Source Software Framework Supporting Scenario Simulations in Bioterrorist Crises

Abstract: Since the 2001 anthrax attack in the United States, awareness of threats originating from bioterrorism has grown. This led internationally to increased research efforts to improve knowledge of and approaches to protecting human and animal populations against the threat from such attacks. A collaborative effort in this context is the extension of the open-source Spatiotemporal Epidemiological Modeler (STEM) simulation and modeling software for agro- or bioterrorist crisis scenarios. STEM, originally designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Closer to our approach are computational modelling tools for epidemiology such as FluTe [46], GLEAMviz [47], STEM [48] and FRED [49]. These solutions use dedicated approaches to model the transmission of infectious disease and provide a graphical user interface (GUI) to specify and visualise an epidemiological model.…”
Section: Discussionmentioning
confidence: 99%
“…Closer to our approach are computational modelling tools for epidemiology such as FluTe [46], GLEAMviz [47], STEM [48] and FRED [49]. These solutions use dedicated approaches to model the transmission of infectious disease and provide a graphical user interface (GUI) to specify and visualise an epidemiological model.…”
Section: Discussionmentioning
confidence: 99%
“…Closer to our approach are computational modelling tools for epidemiology such as FluTe [50], GLEAMviz [51], STEM [52] and FRED [53]. These solutions use dedicated approaches to model the transmission of infectious disease and provide a graphical user interface (GUI) to specify and visualise an epidemiological model.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to solutions that only focus on stochastic simulations (such as GLEAMviz [51] and STEM [52]) our platform can provide more detailed modelling thanks to the availability of agent-based simulation. Investigation of epidemics at a global scale as provided by GLEAMviz [51], STEM [52] or FRED [53] is also possible in Kendrick. A case study of meta-population model can be found in the additional file S1 provided with this publication.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological modellers have used a variety of tools for constructing models: general programming languages, mathematical modelling languages (Matlab, R, etc. ), libraries targeted to epidemiology such as Epipy 3 -a Python tools for epidemiology, GillespieSSA 4 -an R package for generating stochastic simulation using Gillespie's algorithms (Gillespie 1977) or dedicated modelling software as GLEAMviz (Van den Broeck et al 2011), STEM (Falenski et al 2013), FRED (Grefenstette et al 2013) etc. Such tools use different approaches to model the transmission of infectious diseases.…”
Section: Related Work and Discussionmentioning
confidence: 99%